Analysis of Critical Thinking Level of Students in Surrounding and Area of Circle Based on Elder and Paul's Critical Thinking Theory in View Of Students' Mathematical Ability - Pamungkas, Bayu; Onah, Ifeanyi Sunday; Hamzah, Norhayati; Aradi, Bernadett (Cahaya Ilmu Cendekia Publisher, 2023)
The type of research used in this research is qualitative research. The subjects in this study were students in class VIII A and VIII I of SMP Negeri 9 Surakarta, which consisted of six students. The sampling technique in this study used a purposive sampling technique. The instruments used in this research are interview sheets and test instruments. Qualitative data analysis techniques in this study used the Miles and Huberman method which included data collection, data reduction, data presentation, and drawing conclusions. The results of this study are that the level of critical thinking that can be achieved by research subjects with low mathematical abilities is critical thinking level 1 with characteristics of low mathematical ability in solving mathematical problems on the circumference and area of a circle. Furthermore, the level of critical thinking that can be achieved by research subjects with moderate mathematical abilities is critical thinking level 2. The level of critical thinking that can be achieved by research subjects with high mathematical abilities is critical thinking level 3.